Enzymatic versus chemical deinking of non-impact ink printed paper - Pala, H. (2004)
Enzymatic versus chemical deinking is examined for MOW and photocopy prints. Several enzymatic preparations and two fibre/ink particle separation methods are tested. Deinking was monitored by image analysis and standard pulp and paper characterisation procedures. The effectiveness of the fibre/ink particle separation method depends on the ink particle’s size: for smaller particles a washing step is recommended whereas for larger particles, the use of flotation is necessary. The enzymatic treatment is a competitive alternative for MOW and photocopy paper deinking. However, the process requires the selection of an adequate enzymatic preparation for each paper grade.